Independence of Higher Education Quality Assurance: Criteria, Principles, Realities - Yu. B. Rubin (Moscow Polytechnic University, 2021)
The article substantiates the relevance of the independence principle for the higher education quality assurance. Based on cases from the practice of recognized international agencies, an analysis of the procedures for ensuring their independence from the legitimate interests of the stakeholders in the field of higher education was undertaken. The characteristics of the Russian Federation realities in the field of the higher education quality assurance are given and a rationale for the ways of embedding the procedures of education quality assurance and accreditation of universities in the modern global higher education area is given.